Status of Micronutrient Cations in Arid Irrigated Acid Lime Orchard Soil Profiles in Sikar District of Rajasthan (Indian Journal of Arid Horticulture, 2025)
The present study on the distribution of micronutrient cations in arid irrigated acid lime orchard soil profiles in Sikar district of Rajasthan was conducted during March 2007-2008. The study included the analysis of soil profiles with respect to micronutrients. The available iron ranged between 3.54 to 6.38 mg/kg, available zinc between 0.247 to 1.017 mg/kg, available copper between 0.103 to 0.420 mg/kg, and available manganese between 1.37 to 5.15 mg/kg. All the micronutrients were found to be low to medium in range.
Keywords: Acid lime; Orchards; Micronutrients